Karyotype and male internal Reproductive System of Aetalion reticulatum L. (Aetalionidae, Cicadelloidea, Cicadina): Phylogenetic Aspects. - Kuznetsova, Valentina G.; Kirillova, Vera I. (Contributions to Entomology = Beiträge zur Entomologie, 1993)
The first data on anatomy of male reproductive system and karyology of the family Aetalionidae, the most primitive one among the Cicadelloidea, have been obtained. Males of Aetalion reticulatum L. have 9 follicles in each of the paired testes, short accessory glands apparently fromed by twisted tubules, 2n=21, XO. - Tolania opponens Walk.? (a species of a primitive genus of an uncertain tyxonomical position) has been found to have 8 follicles and 2n=21, XO. Such a karyotype, earlier found in other primitive representatives of the Cicadelloidea is regarded as the initial one for the whole superfamily (Emeljanov, Kirillova, 1989). The last view is supperted by our data.